Characterisation of tumour microenvironment remodelling following oncogene inhibition in preclinical studies with imaging mass cytometry - Febe van Maldegem (Nature Portfolio, 2021)
The tumour microenvironment (TME) may change in response to cancer treatments such as KRAS G12C inhibition, with potential implications for combination therapies. Here, the authors provide an antibody panel and workflow for analysing the TME with imaging mass cytometry in pre-clinical mouse models.